2017
DOI: 10.1007/s13105-017-0571-3
|View full text |Cite
|
Sign up to set email alerts
|

Low serum diamine oxidase (DAO) activity levels in patients with migraine

Abstract: Histamine intolerance is a disorder in the homeostasis of histamine due to a reduced intestinal degradation of this amine, mainly caused by a deficiency in the enzyme diamine oxidase (DAO). Among the several multi-faced symptoms associated with histamine intolerance, headache is one of the most recognized and disabling consequences. The aim of this study was to determine the prevalence of DAO deficiency in patients with a confirmed migraine diagnosis according to the current International Headache Society (IHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 32 publications
4
26
0
1
Order By: Relevance
“…Klockler et al found no differences in plasma DAO activity between men and women, although the number of individuals considered was scarce (n = 28) [ 93 ]. Likewise, the study performed by Izquierdo et al reported similar percentages of DAO deficiency in migraine-suffering women (83%) and men (90%) [ 66 ]. On the contrary, García-Martín et al did describe differences in plasma DAO activity by gender, with the prevalence of this enzyme deficiency being higher in women [ 94 ].…”
Section: Histamine Intolerancementioning
confidence: 73%
See 2 more Smart Citations
“…Klockler et al found no differences in plasma DAO activity between men and women, although the number of individuals considered was scarce (n = 28) [ 93 ]. Likewise, the study performed by Izquierdo et al reported similar percentages of DAO deficiency in migraine-suffering women (83%) and men (90%) [ 66 ]. On the contrary, García-Martín et al did describe differences in plasma DAO activity by gender, with the prevalence of this enzyme deficiency being higher in women [ 94 ].…”
Section: Histamine Intolerancementioning
confidence: 73%
“…As mentioned in previous sections, the main barrier against exogenous histamine in the intestines is the DAO enzyme, which prevents its passage into the systemic circulation [ 10 , 13 , 65 ]. Numerous clinical studies have provided data on the prevalence of low plasma DAO levels in individuals showing symptoms of histamine intolerance, mainly headaches and gastrointestinal or dermatological disorders [ 66 ]. Although certain studies have limitations, either in the design or number of participants, the majority point to an association between symptoms and DAO deficiency, establishing a general trend that supports the key role of DAO in the etiology of these disorders.…”
Section: Histamine Intolerancementioning
confidence: 99%
See 1 more Smart Citation
“…hDAO has a central role in histamine intolerance, which is caused by histamine-rich food, alcohol, or drugs that release histamine or inhibit hDAO and, thus, leads to an excess of histamine and symptoms similar to an allergic reaction in the patients [26]. hDAO deficiency has been described in patients with atopic eczema, chronic urticaria, chronic abdominal pain or inflammatory bowel disease, migraines, and asthma [94][95][96][97][98][99]. Histamine also induces contractions and spontaneous abortions when injected into pregnant animals [28,[100][101][102].…”
Section: Biological Functionmentioning
confidence: 99%
“…Inhibition of DAO can also increase the risk of developing intestinal carcinoma, indicating that prolonged use of drugs inhibiting DAO may elevate the cancer risk [111,112]. The patients of atopic eczema, chronic urticaria, chronic abdominal pain or inflammatory bowel disease, migraines, and asthma [94][95][96][97][98][99] that have hDAO deficiency, as well as pregnant women, form high-risk groups for severe ADRs if treated with drugs causing histamine release or drugs having an off-target and activity-blocking effect on hDAO. Currently, aminoguanidine, berenil, pentamidine, and metformin have been indicated to have off-target, activity-blocking effects on hDAO, but many more drugs are expected to show similar behavior, thereby potentially causing severe ADRs [13,27,113].…”
Section: Off-target Functionmentioning
confidence: 99%